2021
DOI: 10.5751/ace-01841-160115
|View full text |Cite
|
Sign up to set email alerts
|

Post-collision impacts, crippling bias, and environmental bias in a study of Newell's Shearwater and Hawaiian Petrel powerline collisions

Abstract: Powerline collisions have been identified on Kaua'i as a potential contributing factor to the large-scale decline of both Hawaiian Petrel (Pterodroma sandwichensis) and Newell's Shearwater (Puffinus newelli), but the scale of the powerline collision problem is unknown. From 2012 to 2020 we conducted observations for seabird powerline collisions across Kaua'i, documented grounded seabirds, and assessed crippling and environmental biases -both poorly studied facets of powerline collision research. We directly ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Because even small errors in avoidance rates for these types of structures can have a very large effect on predicted fatality rates from preconstruction studies (Chamberlain et al 2006, understanding the avoidance behavior of birds around these structures will be especially important in assessing the potential effects of those structures on birds, especially on endangered species such as Hawaiian Petrels and Newell's Shearwaters. Although it is clear from several studies that both Hawaiian Petrels and Newell's Shearwaters collide with transmission lines on Kaua'i (Cooper and Day 1998, Podolsky et al 1998, Travers et al 2021, we found that, during the peak evening and morning activity periods, a substantial proportion of petrels and a small proportion of shearwaters detect and respond to coastal and near-coastal transmission lines under normal ranges of weather conditions and visibility. We agree with others (Chamberlain et al 2006, however, that detailed avoidance data are needed to understand and model fatality risk with confidence.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…Because even small errors in avoidance rates for these types of structures can have a very large effect on predicted fatality rates from preconstruction studies (Chamberlain et al 2006, understanding the avoidance behavior of birds around these structures will be especially important in assessing the potential effects of those structures on birds, especially on endangered species such as Hawaiian Petrels and Newell's Shearwaters. Although it is clear from several studies that both Hawaiian Petrels and Newell's Shearwaters collide with transmission lines on Kaua'i (Cooper and Day 1998, Podolsky et al 1998, Travers et al 2021, we found that, during the peak evening and morning activity periods, a substantial proportion of petrels and a small proportion of shearwaters detect and respond to coastal and near-coastal transmission lines under normal ranges of weather conditions and visibility. We agree with others (Chamberlain et al 2006, however, that detailed avoidance data are needed to understand and model fatality risk with confidence.…”
Section: Discussioncontrasting
confidence: 87%
“…It is clear that collision rates are low, both at these coastal and near-coastal transmission lines and at the mostly inland lines studied by Travers et al (2021). We recorded only one collision in 2,106 total Hawaiian Petrels, Newell's Shearwaters, unidentified shearwaters, and unidentified petrels/shearwaters seen flying near lines on 637 sampling sessions during ∼300 h of sampling, suggesting that collisions may be on the order of ∼0.0005 collisions/bird seen near a coastal or nearcoastal transmission line and ∼0.003 collisions/h of sampling effort.…”
Section: Collision-avoidance In Petrels and Shearwatersmentioning
confidence: 86%
See 3 more Smart Citations